Notes on the systematic placement of Eutheia siamensis Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Examination of the type series (holotype and single paratype) of Eutheia siamensis Franz (Thailand) revealed that it was composed of two different species, belonging not only in different genera, but also tribes. The holotype is a representative of Cephennomicrus Reitter (Cephenniini), while the paratype is a species of Paraneseuthia Franz (Eutheiini). Consequently, E. siamensis is redescribed as Cephennomicrus siamensis (Franz), comb. n.; and the paratype Paraneseuthia is illustrated, but the specimen is probably a female, and remains as an undescribed species. Cephennomicrus has already been recorded from Thailand, but Paraneseuthia is reported to occur in this country for the first time, filling a distributional gap between Far Eastern, Sundaland/Australian and recently discovered Himalayan and Turkish species of this interesting genus.